Advancing and Consolidating Mathematical Modelling Research from ICME-14 - Greefrath, Gilbert; Carreira, Susana; Stillman, Gloria Ann (International Perspectives on the Teaching and Learning of Mathematical Modelling, 2023)
XIII, 348 p. 61 illus., 34 illus. in color.